Cloning, characterization and functional analysis of NtMYB306a gene reveals its role in wax alkane biosynthesis of tobacco trichomes and stress tolerance - Yu, Jing; Lei, Bo; Zhao, Huina; Wang, Bing; Kakar, Kaleem U.; Guo, Yushuang; Zhang, Xiaolian; Jia, Mengao; Yang, Hui; Zhao, Degang (Frontiers in Plant Science, 2022)
Trichomes are specialized hair-like organs found on epidermal cells of many terrestrial plants, which protect plant from excessive transpiration and numerous abiotic and biotic stresses. However, the genetic basis and underlying mechanisms are largely unknown in Nicotiana tabacum (common tobacco), an established model system for genetic engineering and plant breeding. In present study, we identified, cloned and characterized an unknown function transcription factor NtMYB306a from tobacco cultivar K326 trichomes. Results obtained from sequence phylogenetic tree analysis showed that NtMYB306a-encoded protein belongs to S1 subgroup of the plants’ R2R3-MYB transcription factors (TFs). Observation of the green fluorescent signals from NtMYB306a-GFP fusion protein construct exhibited that NtMYB306a is localized in nucleus. In Yeast transactivation assays, the transformed yeast containing pGBKT7-NtMYB306a construct was able to grow on SD/-Trp-Ade+X-α-gal selection media, signifying that NtMYB306a exhibits transcriptional activation activity. Results from qRT-PCR, in-situ hybridization and GUS staining of transgenic tobacco plants revealed that NtMYB306a is primarily expressed in tobacco trichomes, especially tall glandular trichomes (TGTs) and short glandular trichomes (SGTs). RNA sequencing (RNA-seq) and qRT-PCR analysis of the NtMYB306a-overexpressing transgenic tobacco line revealed that NtMYB306a activates the expression of a set of key target genes which are associated with wax alkane biosynthesis. Gas Chromatography–Mass Spectrometry (GC-MS) exhibited that the total alkane contents and the contents of n-C28, n-C29, n-C31, and ai-C31 alkanes in leaf exudates of NtMYB306a-OE lines (OE-3, OE-13, and OE-20) were significantly greater when compared to WT. Besides, the promoter region of NtMYB306a contained numerous stress-responsive cis-acting elements, and their differential expression towards salicylic acid and cold stress treatments reflected their role in signal transduction and cold-stress tolerance. Together, these results suggest that NtMYB306a is necessarily a positive regulator of alkane metabolism in tobacco trichomes that does not affect the number and morphology of tobacco trichomes, and that it can be used as a candidate gene for improving stress resistance and the quality of tobacco.